Non-Medical prescribing policies: A global scoping review. Issue 7 (July 2020) - Ecker, Sarah; Joshi, Rohina; Shanthosh, Janani; Ma, Chenjuan; Webster, Ruth
Highlights: Autonomous non-medical prescribing rights are found in a majority of countries, globally. Highest and lowest physician to population ratios are associated with allowing non-medical prescribing rights. Low and lower middle income countries, have the highest rate of available legislation on non-medical prescribing rights. Abstract: Background: Authorizing health care providers other than physicians to prescribe medicines (i.e., non-medical prescribing, NMP) has been used to improve access to healthcare in many countries. This paper aimed to identify the scope of policies facilitating NMP worldwide and investigate the relationship of such policies with a country's physician to population ratio and economic status. Methods: A hierarchical search strategy was used. First, we compiled a list of countries and territories ( n = 216) based upon World Bank record. Then, we collected relevant information for each country by using country name combined with key terms in PubMed, Google, and World Health Organization (WHO) country pharmaceutical profiles. Countries' socio-economic status and physician to population ratio were determined using data from the World Bank. Results: Legislation allowing NMP was found for 117 of 216 (54%) countries and territories. The most prevalent policy identified was that of autonomous prescribing authority (59%). Countries with low or high incomes and those with low or high physician to population ratios (<1/1000 or >3/1000) had the highest concentration of policies for NMP rights. Conclusion: Despite the varied scope of relevant policies, NMP has been implemented in countries of varied income levels and physician to population ratios. Future research is warranted to empirically examine its impact on access to care.